Chinese refugee children and empires: the politics of international adoptions in cold war Hong Kong - Franco, Rosaria (Taylor & Francis, 2018)
With the support of new sources from British and Hong Kong archives, this study casts new light on the post-war international adoptions of Chinese refugee children in the British colony of Hong Kong. It argues that while children were ‘saved’ and found families overseas, they were also used as pawns in a bigger political game. A way to delegate welfare for the Hong Kong government, a symbolic humanitarian concession vis-à-vis a strict anti-immigration policy for Britain, and an anti-communist propaganda tool for the United States, these adoptions also convey the competing power and population politics played over subject children by two multiracial empires: one in decline (the rapidly decolonising Britain), the other on the rise (the new cold war superpower).